Anthropological Dimension of Commemorative Practices: The Phenomenon of Bodily Memory - I. M. Bondarevych (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The article is aimed to analyse the phenomenon of bodily memory in the context of commemorative practices. The commemorative practices are a social instrument known since archaic times, which had different ways of use in different epochs. In totalitarian societies, officially organized commemorative practices are frequently used for propaganda and manipulation. For most people, their mechanism remains unconscious, as bodily memory plays a leading role there. The density of a modern social world actualises the ability to observe own changes and regulate the processes of their flow. This updates an exploration of the bodily memory phenomenon. Theoretical basis. The classification of forms of bodily memory is carried out in the article: genetic (cellular memory, heredity), psychophysical (memory for different types of sensations, skills, muscle tone, etc.), psychoenergetic (emotions, mental states, mood, unconscious action, etc.), mental (knowledge of the rules of social games, attitudes, stereotypes, thoughts, memories, ways of our detection, behaviour, etc.). It has been revealed that the systemic openness of bodily memory is the fundamental basis of commemorative practices. Originality. The term "conscious commemoration" is proposed to denote the anthropological process associated with self-knowledge, self-construction and co-creation, which requires a distinction between forms of bodily memory, understanding of its structural features and functional capabilities. Conclusions. The phenomenon of bodily memory reveals the anthropological potential of commemorative practices. It can manifest itself as an independently organized body-spiritual practice of self-construction (harmonization of the architecture of one’s own body and individuality) on the basis of self-knowledge and self-observation (directing attention to one’s movements, reactions, behaviour, honest recognition of one’s attitudes). The latter is the foundation of conscious co-creation. The phenomenon of bodily memory reveals the secret of spiritualization in the process of approaching a person to his body.